Educational Game as An Effort to Accelerate Learning After The Covid-19 Pandemic - Khairul Umam Syaliman; Nina Fadilah Najwa; Jan Alif Kreshna (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
The Covid-19 pandemic that occurred forced us to carry out the learning process through the internet network (online or online). Learning carried out online creates many problems, so it is considered ineffective and causes learning loss. Various methods have been taken to overcome this learning loss, including collaborating with various parties and issuing various regulations. In addition, teachers are also required to provide a new spirit in creating and innovating to provide effective, efficient, and competitive learning media. One way is to do educational game-based learning. Educational games are considered adequate for overcoming learning losses because learning media with educational games require players to participate in determining outcomes, have an entertainment side, and can increase creativity and problem-solving skills. The planned research method stages for collecting the required data are observation, interviews, and literature study. As for the development of educational games in this study, the prototype development method will be used. This study's result is that the Educational Game design has produced output that meets the needs. In future research, when this design is implemented, it is hoped that it will be an alternative medium for accelerating post-pandemic learning.